2020
DOI: 10.3390/cancers12113197
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Combining Immunotherapy with Radiotherapy in Recurrent/Metastatic Head and Neck Cancer

Abstract: Immunotherapy with immune checkpoint inhibitors (ICI) has recently become a standard part of the treatment of recurrent or metastatic head and neck squamous cell carcinoma (R/M HNSCC), although the response rates are low. Numerous preclinical and clinical studies have now illuminated several mechanisms by which radiotherapy (RT) enhances the effect of ICI. From RT-induced immunogenic cancer cell death to its effect on the tumor microenvironment and vasculature, the involved mechanisms are diverse and intertwin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 177 publications
0
14
0
Order By: Relevance
“…Patients with HNSCC are very susceptible to recurrent or new tumors, which are the main cause of death ( Plavc et al, 2020 ). Tumor recurrence was attributed to lateral invasion of small tumor nests beneath the surface epithelium, but the mechanism of lateral invasion is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with HNSCC are very susceptible to recurrent or new tumors, which are the main cause of death ( Plavc et al, 2020 ). Tumor recurrence was attributed to lateral invasion of small tumor nests beneath the surface epithelium, but the mechanism of lateral invasion is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent/new tumors and metastasis are the main causes of death in patients with HNSCC; these secondary tumors often metastasize and respond poorly to treatment ( Takes et al, 2012 ; Ruzevick et al, 2013 ; Plavc et al, 2020 ). Thus, discovery of biological factors that regulate invasion in HNSCC is essential for identifying new treatment strategies and improving survival, with possible implications for other epithelial-derived tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Although some clinical studies have confirmed the phenomenon of local RT combined with immunotherapy to stimulate abscopal response, the optimal combination strategy of RT combined with immunotherapy still needs to be further explored (145)(146)(147), including: (1) What are the best sequences to follow when combing RT with immunotherapy? Different studies have shown that the optimal timing of immunotherapy combined with RT is different, which is still controversial at present.…”
Section: Prospects and Challenges Of Combined Immunotherapy With Radi...mentioning
confidence: 99%
“…The implications of other factors including the microbiome in the synergistic effect of radiotherapy and immunotherapy are still little known. In the context of this new possible indication of radiotherapy, the identification of biomarkers both for the response to treatment with ICI or for radiotherapy–immunotherapy combination is one of maximum interest [ 94 , 95 ].…”
Section: Mirna In Head and Neck Cancers—from The Biomarker Of The Fut...mentioning
confidence: 99%